If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + 4x = -16 + x Solving 2 + 4x = -16 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 2 + 4x + -1x = -16 + x + -1x Combine like terms: 4x + -1x = 3x 2 + 3x = -16 + x + -1x Combine like terms: x + -1x = 0 2 + 3x = -16 + 0 2 + 3x = -16 Add '-2' to each side of the equation. 2 + -2 + 3x = -16 + -2 Combine like terms: 2 + -2 = 0 0 + 3x = -16 + -2 3x = -16 + -2 Combine like terms: -16 + -2 = -18 3x = -18 Divide each side by '3'. x = -6 Simplifying x = -6
| 73y=8(9y+10) | | 5c-3=5x-(x+2)-1 | | N=0.5s+-1z | | 7-1/2x=-4 | | 8x-75=5x-12 | | 5x-18=y | | 5y^2-13y-28= | | 1x-1=5x-4x-4+25 | | -99/x=2 | | 3x+19=56 | | V=(24-2x)(18-2x)x | | -3x+14=-7 | | 9x+7y=19.7 | | 6r^4/r^7 | | 2e^3x-1=e^2x+1 | | 3(3x+5y)-9x-7y=3(19.825)-19.7 | | 2x(x-3)=8(x-3) | | X^8/x^9 | | -8-3=10x+3-9x | | 11x-9y-10= | | a*3+5=12 | | 4x(3x^3y^4)= | | I=F-IR | | 2x^2-20x-48= | | 5x+6x-3=21 | | F-IR=I | | 7/9-3/18 | | F=i+ir | | x^2+3x-2012=0 | | (w)(w+7)=0 | | x-18sqrtx+80=0 | | I=f-1ir |